Pengaruh Citra Merk dan Inovasi Produk terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan Sebagai Variabel Mediasi Pada Konsumen Indomie di Surakarta - Pradana, Muhammad Aldilo Ihza; Achmad, Nur (Jurnal Informatika Ekonomi Bisnis, 2023)
In the current era of rapid development, it has an impact on the development of increasingly developed and competitive business types, which requires companies to always strive to increase market share and reach consumers. This study aims to determine the effect of brand image and product innovation on customer loyalty with customer satisfaction as a mediating variable for Indomie consumers in Surakarta. Respondents in this study were 140 respondents who were conducted through online surveys with Google forms. The sampling technique used purposive sampling technique. Test the validity and reliability using smart PLS analysis on the outer model. Hypothesis testing uses the smartPLS inner model. The results of the analysis show that customer satisfaction partially mediates the relationship between brand image and product innovation on customer loyalty.